The effects of 17?-estradiol and vitamin E treatments on oxidative stress and antioxidant levels in brain cortex of diabetic ovariectomized rats - Ulas, M.; Cay, M. (Akademiai Kiado Rt, 2010)
We investigated the effects of 17 beta-estradiol (E-2) and vitamin E on lipid peroxidation and antioxidant levels in brain cortex of diabetic ovariectomized (OVX) rats. Forty-two rats were equally divided into seven groups: Control; OVX; OVX+E-2; OVX+E-2+vitamin E; OVX+diabetic; OVX+diabetic+E-2 and OVX+diabetic+E-2+vitamin E. Then, E-2 (40 mu g kg(-1)/day) and vitamin E (100 mg kg(-1)/day) were given. Glutathione peroxidase (GSH-Px), catalase (CAT), superoxide dismutase (SOD), glutathione (GSH), vitamin A and beta-carotene in brain were decreased (p<0.05) when compared with control in OVX but MDA in brain and glucose in plasma were elevated (p<0.05). The antioxidant levels in brain (p<0.05) increased although MDA (p<0.05) in brain and glucose (p<0.05, p<0.01) in plasma decreased in OVX after E-2 and E-2+vitamin E supplementation. The activities of GSH-Px (p<0.001, p<0.01), CAT (p<005, p<0.001) and SOD (p<0.001) and the levels of GSH (p<0.001), vitamin A (p<0.05) and beta-carotene (p<0.001, p<0.05) were lower in the brain of OVX diabetic rats, while MDA in the brain and glucose in the plasma were higher (p<0.001). The antioxidant enzymes (p<0.05, p<0.01), GSH, vitamin A and beta-carotene (p<0.01, p<0.001) in brain increased while MDA in brain and glucose in plasma decreased (p<0.01, p<0.001) in diabetic OVX after treatments. Finally, the E-2 and E-2+vitamin E supplementation to diabetic OVX and OVX rats may strengthen the antioxidant system by reducing lipid peroxidation.
Keywords: ovariectomy; catalase; glutathione peroxidase; streptozotocin; diabetes mellitus; antioxidant level; 17 beta-estradiol; vitamin E; oxidative stress; brain cortex